Knowledge, attitude and practices of medical students regarding biomedical waste management - Khan, Fatima; Khan, Jowairiya; Khursheed, Manal; Sultan, Asfia; Khan, Haris (Journal of Patient Safety and Infection Control, 2021)
Context: India generates around 3 million tonnes of medical wastes every year, an amount that is expected to grow at 8% annually. Improper handling of biomedical waste (BMW) can result in the spread of infections such as HIV-acquired immunodeficiency syndrome, hepatitis B virus and hepatitis C virus in addition to being a burden on the environment. Segregation being the most important step in BMW management (BMWM) necessitates that people working in the health-care system are aware of its rules and regulations. Therefore, it is important to understand and explore any lacunae in knowledge, attitudes and practices regarding BMWM. Aim: The aim of this study is to develop an insight into the knowledge, attitude and practices of medical students regarding BMWM. Settings and Design: An institutional-based cross-sectional study with a quantitative approach was conducted. Subjects and Methods: A structured questionnaire prepared according to the knowledge, attitude and practices (KAP) model. Statistical Analysis Used: Data were analysed by the IBM SPSS (Statistical Package for the Social Sciences), v20.0 software. Results: The participants' knowledge on BMWM was scored on a scale of 0-50. Thirty-six per cent of them scored in the range of 20-30, while 30.9% scored between 30 and 40. Three-fourths of them believed that it was important to be aware of BMW generation, hazards and legislation. About 87.09% opined that soft skills regarding BMWM should be a part of the curriculum for health-care students. About 76% of the respondents claimed to follow colour coding while discarding BMW. About 41.3% of the participants responded that they would report anyone found breaking the rules of BMWM. Conclusions: The study revealed that there is still a significant lack in the KAP of health-care students regarding BMWM.